Analisis Sentimen Positif Terhadap Brand Kecantikan Avoskin sebagai Eco Friendly Brand di Media Sosial X dan TikTok - Magrifatul Zania Maharani; Hafiar, Hanny; Chandratama Priyatna, Centurion (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
The Indonesian beauty industry continues to grow, marked by the emergence of many local skincare brands. Avoskin is a local skincare brand that is committed to